2012
DOI: 10.1117/12.974598
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of snow pack characteristics by means of polarimetric SAR data

Abstract: Characterization of the snow-pack is fundamental for several applications in hydrology, such as modelling and\ud forecasting of snow melt runoff, water resource management and risk analysis. Thanks to its night/day capabilities and\ud weather conditions independence, Synthetic Aperture Radar (SAR) represents a valuable tool for snow monitoring,\ud especially in mountain areas often covered by clouds.\ud The goal of the research project presented in this communication is to investigate the sensitivity of fully … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Singh et al [30] found that snow-covered regions show lower entropy, H(1-A) as well as higher polarimetric anisotropy; thus they proposed a threshold method to detect snow cover, which resulted in an accuracy comparable to a supervised Wishart classification. Reppucci et al [167] observed that dry snow is characterized by higher values in the Pauli surface parameter and lower value in the double-bounce parameter. Therefore, a combination of the two parameters enables to calculate the difference and then to map dry snow cover.…”
Section: Wet and Dry Sce Detectionmentioning
confidence: 99%
See 3 more Smart Citations
“…Singh et al [30] found that snow-covered regions show lower entropy, H(1-A) as well as higher polarimetric anisotropy; thus they proposed a threshold method to detect snow cover, which resulted in an accuracy comparable to a supervised Wishart classification. Reppucci et al [167] observed that dry snow is characterized by higher values in the Pauli surface parameter and lower value in the double-bounce parameter. Therefore, a combination of the two parameters enables to calculate the difference and then to map dry snow cover.…”
Section: Wet and Dry Sce Detectionmentioning
confidence: 99%
“…Hence, almost all studies calculated the mask during the geocoding step and later re-used it to mask out the results, as illustrated in Figure 6. However, these terrain-induced radiometric effects and the local illuminated brightness should be In addition to conventional confusion matrix-based accuracy evaluations, Luojus et al [139,175] proposed a quantitative analysis approach based on the RMSE to check the improvement made by each refining algorithm; Reppucci et al [167] compared the resultant SCE with an elevation map to check whether the distribution of snow is reasonable.…”
Section: Digital Elevation Model Influence Of Topography On Sar-basementioning
confidence: 99%
See 2 more Smart Citations